The Effect of Acanthus Ilicifilius Extract On Anticandida Albicans Antibody in Wistar Rats with Oral Candidiasis Immunosupressed Model - Dwi Andriani; Dwi Setianingtyas; Nafi’ah (Denta Journal Kedokteran Gigi, 2017)
Background: Candida albicans (C.Albicans) causes oral candidiasis. Candida adhesion proteins stimulate the immune system to eliminate C.albicans chloroform extract of acanthus leaves ilicifolius have inhibitory against C.Albicans. Purpose: To proved the potential Acanthus ilicifolius (A.ilicifolius) extract to inhibit the growth of C.Albicans in rats with oral candidiasis. Materials and Methods: This study was true experimental with post test only control group design. Wistar rats were used and imunosupressed with dexamethasone and ditetrasiklin peroral after that induced by C.albicans 6x108 on the tongue of rats for14 days. Divided into five groups, healthy (G1), candidiasis (G2), treatment group 1 (G3): candidiasis + nystatin, Treatment 2 (G4): candidiasis+extract A.Ilicifollius 8%, and Treatment 3 (G5) : candidiasis+extract A.Ilicifollius 16%. The rats was treated for 14 days after induction of candida. A.Ilicifollius chloroform extraction method was maceration. Samples was processed immunohistochemistry staining methods and added antibody anticandida albicans (IgG mouse). Observed the results using microscope (magnification 400x). Data were analyzed with the Kruskal-Wallis and Mann Whitney. Results: There was significant differences between G1 with G2, G3, G4, G5 (p˂0,05). There was significant difference between G2 to G3, G4 and G5 (p˂0,05). There was no significant difference between G3, G4, and G5 (p˃0,05). Conclusion. A.ilicifollius extract have potential to inhibit the growth of Candida albicans in rats with oral candidiasis.